O historial clínico do Homem dos lobos de Freud, revisitado à luz de certos aportes da psicanálise contemporânea. Muito aquém da neurose - Lisondo, Alicia Beatriz Dorado de (Revista de Psicanálise da SPPA, 2020)
O historial clínico do Homem dos lobos de Freud (1918 [1914]) é revisitado à luz de certos aportes da psicanálise contemporânea: contratransferência; campo analítico; o terceiro analítico; trabalho do sonho alfa do analista; a pessoa do analista; a cena primária; transformações em “O”; a mente multidimensional. O diagnóstico de neurose também é reformulado (Bion, 1957), considerando os aportes dos autores que estudaram as patologias não neuróticas (Green, 1988, 1995, 2005; Roussillon, 2019; Lutemberg, 2007, 2008; Levine, Reed e Scarfone, 2015), com déficit na simbolização, o vazio mental, os transtornos do psico-soma (Winnicott, 1965/1983; Green, 1988, 2005b, 2005c; Roussillon, 2019; Liberman et al., 1982; Marty, 1993, 1998), às defesas obsessivas e os estados autistas da mente (Korbivcher, 2013) (AU) Abstract The clinical history of Freud’s Wolf man revisited in the light of certain contributions from contemporary psychoanalysis. Far from neurosis The clinical history of Freud’s Wolf man (1918 [1914]) is revisited in light of certain contributions of contemporary psychoanalysis: countertransference; analytical field; the third analytic; analyst’s alpha dream work; the person of the analyst; the primary scene, O-transformations; and the multidimensional mind. The diagnosis of neurosis is also reformulated (Bion, 1957), considering the contributions of the authors who studied non-neurotic disorders (Green, 1988, 1995, 2005; Roussillon, 2019; Lutemberg, 2007, 2008; Levine, Reed and Scarfone, 2015), with a deficit in symbolization, mental emptiness, psycho-soma disorders (Winnicott, 1965/1983; Green, 1988, 2005b, 2005c; Roussillon, 2019; Liberman et al., 1982; Marty, 1993, 1998), to obsessive defenses and autistic states of mind (Korbivcher, 2013). Keywords: Wolf man; Technique; Primary scene; Contemporary psychoanalysis; Nonneurotic disorders Resumen El historial clínico del Hombre de los lobos de Freud, revisitado a la luz de ciertas contribuciones del psicoanálisis contemporáneo. Muy por debajo de la neurosis El historial clínico del Hombre de los lobos de Freud (1918 [1914]) es revisitado a la luz de ciertas contribuciones del psicoanálisis contemporáneo: contratransferência; campo analítico; el tercer analítico; trabajo del sueño alfa del analista; la persona del analista; la escena primaria; las transformaciones en “O”; y la mente multidimensional. El diagnóstico de neurosis también se ha reformulado (Bion, 1957), teniendo en cuenta las contribuciones de los autores que estudiaron las patologías no neuróticas (Green, 1988, 1995, 2005; Roussillon, 2019; Lutemberg, 2007, 2008; Levine, Reed y Scarfone, 2015), con déficit en la simbolización, vacío mental, trastornos del psicosoma (Winnicott, 1965/1983; Green, 1988, 2005b, 2005c; Roussillon, 2019; Liberman et al., 1982; Marty, 1993, 1998), defensas obsesivas y estados mentales autistas (Korbivcher, 2013). Palabras clave: Hombre de los lobos; Técnica; Escena primaria; Psicoanálisis contemporánea; Patologías no neuróticas